Fraud Prevention through ASN Competence, IT Quality, Internal Control, and Good Governance: A Systematic Literature Review - Rifqi, Muhammad; Djaddang, Syahril (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
This study aims to analyze the factors influencing fraud prevention in the public sector through a Systematic Literature Review (SLR) approach. The review focuses on four key variables: civil servant competence, information technology quality, internal control, and good governance principles. The study applied the SLR method following Kitchenham (2004) and PRISMA (2020) guidelines through four main stages: identification, screening, eligibility, and inclusion. Out of 120 initially identified articles, 16 met the inclusion criteria and were further analyzed. The findings reveal that civil servant competence, information technology quality, and internal control positively affect fraud prevention. Moreover, good governance acts as a moderating variable that strengthens these relationships. The study emphasizes the importance of improving civil servants’ professionalism and integrity, reliable information technology implementation, and internal control systems aligned with good governance principles.